2024
DOI: 10.1007/s10533-023-01110-2
|View full text |Cite
|
Sign up to set email alerts
|

Degradation increases peat greenhouse gas emissions in undrained tropical peat swamp forests

Erin Swails,
Steve Frolking,
Jia Deng
et al.

Abstract: Tropical peat swamp degradation can modify net peat greenhouse gas (GHG) emissions even without drainage. However, current Intergovernmental Panel on Climate Change (IPCC) guidelines do not provide default emission factors (EF) for anthropogenically-degraded undrained organic soils. We reviewed published field measurements of peat GHG fluxes in undrained undegraded and degraded peat swamp forests in Southeast Asia (SEA) and Latin America and the Caribbean (LAC). Degradation without drainage shifted the peat fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…Estimating onsite peat CO 2 emissions following IPCC guidelines requires values for both carbon loss via heterotrophic respiration and the carbon input from litterfall and root mortality. Applying literature values for carbon inputs and soil respiration partitioning ratios specific to peatlands in Southeast Asia 38 , we estimate that the peat onsite CO 2 budget for the PPSF is − 25.1 ± 7.5 MgCO 2 e ha −1 yr −1 and for the SPSF is – 22.0 ± 5.6 MgCO 2 e ha −1 yr −1 (Table 5 ). These estimates for the potential onsite CO 2 sink for the PPSF and SPSF are much larger than those reported for undegraded and degraded undrained peatlands in Southeast Asia 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimating onsite peat CO 2 emissions following IPCC guidelines requires values for both carbon loss via heterotrophic respiration and the carbon input from litterfall and root mortality. Applying literature values for carbon inputs and soil respiration partitioning ratios specific to peatlands in Southeast Asia 38 , we estimate that the peat onsite CO 2 budget for the PPSF is − 25.1 ± 7.5 MgCO 2 e ha −1 yr −1 and for the SPSF is – 22.0 ± 5.6 MgCO 2 e ha −1 yr −1 (Table 5 ). These estimates for the potential onsite CO 2 sink for the PPSF and SPSF are much larger than those reported for undegraded and degraded undrained peatlands in Southeast Asia 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Applying literature values for carbon inputs and soil respiration partitioning ratios specific to peatlands in Southeast Asia 38 , we estimate that the peat onsite CO 2 budget for the PPSF is − 25.1 ± 7.5 MgCO 2 e ha −1 yr −1 and for the SPSF is – 22.0 ± 5.6 MgCO 2 e ha −1 yr −1 (Table 5 ). These estimates for the potential onsite CO 2 sink for the PPSF and SPSF are much larger than those reported for undegraded and degraded undrained peatlands in Southeast Asia 38 . Our higher estimates for the onsite CO 2 sink potential may be due to the lower estimated heterotrophic respiration rates at Muara Siran compared to other undrained peatlands.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to active drainage of tropical swamp forests and subsequent land use change, peatland degradation due to unsustainable harvesting of e.g., Mauritia flexuosa palms for fruit, affects site hydrology and GHG fluxes. A site study for a peat swamp forest in Peru ) and a review of published field measurements by Swails et al (2024) for sites in Southeast Asia, Latin America and the Caribbean provide initial insights into the magnitude of GHG flux changes due to degradation. Swails et al (2024) conclude that "the large observed increases in net CO 2 emissions in undrained degraded forests compared to undegraded conditions calls for their inclusion as a new class in the IPCC guidelines" and that either protection or a new approach to sustainable management of swamp peatlands is needed to limit the impact of tropical peatland degradation on GHG emissions and the climate.…”
mentioning
confidence: 99%